2012
DOI: 10.1007/s10157-012-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity accelerate the progression of IgA nephropathy: prognostic utility of a combination of BMI and histopathological parameters

Abstract: A combination of BMI ≥25 kg/m(2), the Oxford classification M1, and a Max GA ≥42,900 μm(2) can serve as a predictor of long-term renal outcome of IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 29 publications
0
48
0
2
Order By: Relevance
“…These studies are typically described as validation studies, although none prospectively studied new cohorts; nevertheless they provide valuable corroborative evidence. Sixteen such studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , including cohorts from Europe, North America, and East Asia were meta-analysed in a report published in 2013 21 . Lately, more studies have been published including cohorts from Iran, Europe, Japan and Korea [22][23][24][25][26][27][28] .…”
Section: Published Retrospective Validation Studiesmentioning
confidence: 99%
“…These studies are typically described as validation studies, although none prospectively studied new cohorts; nevertheless they provide valuable corroborative evidence. Sixteen such studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , including cohorts from Europe, North America, and East Asia were meta-analysed in a report published in 2013 21 . Lately, more studies have been published including cohorts from Iran, Europe, Japan and Korea [22][23][24][25][26][27][28] .…”
Section: Published Retrospective Validation Studiesmentioning
confidence: 99%
“…Other risk factors are numerous and controversial but not widely confirmed. They include age at disease onset, sex, overweight or obesity, serum albumin, hemoglobin, hypertriglyceridemia or hyperuricemia, and various immunogenetic markers (8)(9)(10)(11)(12)(13)(14). Using these factors, several risk scoring systems have been developed (6,9,15) for evaluating the rate of IgAN progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, urinary protein excretion appeared, followed by a 10 kg weight gain. Recently, Kataoka et al (28) showed a BMI " 25 kg/m 2 to be an independent predictor of disease progression in IgA nephropathy, suggesting that even a mild overweight status might contribute to a progression of renal injury in the setting of renal impairment.…”
Section: Discussionmentioning
confidence: 99%